Augmenting Tendon‐to‐Bone Repair with Functionally Graded Scaffolds. Issue 9 (10th March 2021) - Zhu, Chunlei; Qiu, Jichuan; Thomopoulos, Stavros; Xia, Younan
Abstract: Tendon‐to‐bone repair often fails because the functionally graded attachment is not regenerated during the healing process. Biomimetic scaffolds that recapitulate the unique features of the native tendon‐to‐bone attachment hold great promise for enhancing the healing process. Among various types of scaffolds that are developed and evaluated for tendon‐to‐bone repair, those with gradations (in either a stratified or a continuous fashion) in composition, structure, mechanical properties, and cell phenotype have gained the most attention. In this progress report, the recent efforts in the rational design and fabrication of functionally graded scaffolds based upon electrospun nanofiber mats and inverse opal structures, as well as the evaluation of their applications in augmenting tendon‐to‐bone repair, are reviewed. This report concludes with perspectives on the necessary future steps for clinical translation of the scaffolds. Abstract : This progress report reviews the recent activities in the design and fabrication of functionally graded scaffolds for tendon‐to‐bone repair. The compositional and structural gradations in these scaffolds are anticipated to duplicate various aspects of the native attachment site and thereby promote healing and functional recovery.